Effects of telehealth interventions on performing activities of daily living and maintaining balance in stroke survivors: A systematic review and meta‐analysis of randomised controlled studies. Issue 19 (6th December 2021) - Saragih, Ita Daryanti; Tarihoran, Dame Elysabeth Tuty Arna Uly; Batubara, Sakti Oktaria; Tzeng, Huey‐Ming; Lin, Chia‐Ju
Abstract: Background: Stroke is one of the most common causes of disability worldwide. In recent years, diverse telehealth programmes for stroke survivors have suggested that this mode of rehabilitation could improve stroke survivors' abilities to perform activities of daily living (ADLs) and maintain balance. Although increasingly utilised in clinical and community settings, the effectiveness of telehealth interventions in stroke survivors remains inconclusive. This warrants investigation so that telehealth interventions are evidence‐based and are not merely modalities of convenience. Aim: To identify the effects of telehealth interventions on the ability to perform ADLs and maintain balance in stroke survivors. Design: A systematic literature review and meta‐analysis were conducted in accordance with PRISMA guidelines. Methods: A systematic literature search was performed using seven databases for literature dated up to April 25, 2021. The revised Cochrane risk of bias tool for randomised trials was used to assess the methodological quality of the included studies. A meta‐analysis was performed using a random‐effects model to calculate the pooled effects of telehealth interventions. Stata 16.0 was used for the statistical analyses. Results: A total of 14 studies with 1, 367 participants were included in the analysis. Overall, telehealth interventions were effective in improving stroke survivors' abilities to carry out their ADLs (standardised mean difference: .45; 95% confidence interval: .12 to .78); however, no significant effects were found on balance. Conclusion: Telehealth interventions are beneficial for improving stroke survivors' performance of their ADLs. Future telehealth intervention trials should focus on identifying essential intervention delivery components that facilitate intervention adoption by clinicians and stroke survivors and sustain the positive effects on stroke survivors' performance of their ADLs in different settings. Relevance to clinical practice: It is essential to build flexibility in the telehealth‐based intervention delivery protocol to meet individual stroke survivors' needs to motivate and enhance their ADL performance.